Microglial activation mediates maternal separation-induced depressive-like behavior in rats: A neurodevelopmental depression model - ARICIOĞLU, FEYZA (My University, 2023)
© 2023 The AuthorsBackground: : Maternal Separation (MS) is an early life stress which has been associated with neurological, behavioral, chemical and endocrinological changes in adult life in rats and both short term and long-term mental health disturbances, notably depression in human. This study was planned as a neurodevelopmental depression model, to investigate the possible role of the NLRP3 pathway. Material and Method: : Rat pups were separated from their mothers on their second postnatal day (PND) for 4 h and were placed back in their home cage every day for 21 days. On PND23 they were randomly assigned to either the MS or the MS + imipramine group (receiving 30 mg/kg/day i.p. imipramine for 15 days). Depression-like behaviors were assessed by open field, sucrose preference, forced swimming and elevated plus maze tests. Prefrontal cortex regions were dissected to evaluate NLRP3, ASC and caspase-1 mRNA expressions. Results: : Significant decrease of total activity, sucrose preference as an anhedonia indicator, longer immobilization time in the forced swim test, increased time and the number of entries into the closed arms in elevated plus maze were found in the MS group compared to Control group, and these effects were reversed by imipramine treatment. NLRP3, ASC and caspase-1 mRNA expressions were increased with MS and this increase was suppressed with imipramine treatment. Conclusion: : MS causes depressive-like behaviors in rats and these behavioral changes may be related to the NLRP3 pathway. Imipramine treatment can prevent not only depression-like behaviors, but also neuroinflammation by suppressing NLRP3-mediated mechanisms in the neurodevelopmental depression process.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Clinical Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; PSİKOLOJİ, KLİNİK; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; PSYCHOLOGY, CLINICAL; Klinik Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psikiyatri ve Ruh Sağlığı; Social Sciences & Humanities; Psychiatry and Mental Health; ASC; Caspase-1; Depression; Imipramine; Maternal separation; NLRP3